Journal de bord d’enseignants : sens de cette pratique pour le développement professionnel - Geneviève Tschopp (Recherches en Éducation)
During their career, teachers develop their reflective practice, particularly through written form. Among their writing practices in a professional situation, some have adopted that of the writing logbook. How is it put in place and has it evolved ? What does this writing bring to teachers in terms of professional development and empowerment in particular ? Teachers seem to make little use of writing logbook, while it is expected in initial training, particulary at the High Teaching School of the canton of Vaud with a focus on self-training. This research aims to highlight effects on their professional development and their empowerment. Biographical interviews and explanations will approch the singular experience of people who have integrated this form of writing into their professional gestures.